The Influence of War Photographs and Hoaxes Within Social Media on The Perception of Reality: The Creation Of ‘Fake News’ - Bartscheck, Frank (AUC Knowledge Fountain, 2019)
On September 1, 2017, the BBC Brasil published an article that exposed the Eduardo Martins hoax, which involved an online persona that purported to be a combat photojournalist. The hoaxer was able to deceive multiple stock image banks, as well as several online and mainstream news publications, including The Wall Street Journal and Getty Images. The hoax culminated with the publication of moderately manipulated images that ostensibly depicted conflict in Syria, Iraq and Gaza. With a large portion of the American news cycle dedicated to examining the phenomena of fake news, this hoax presented an opportunity for the news media to examine contemporary newsgathering procedures and image indexicality. Yet, beyond the initial disclosure by BBC Brasil, no American journalistic resources were dedicated to investigating this hoax. The lack of any follow-up investigation into an event that spoke directly to contemporary newsgathering procedures and photographic veracity exposes uncomfortable truths within contemporary news media. The revelation of a widespread image-based hoax deceiving mainstream and trusted news arbiters in America, and subsequent lack of journalistic attentiveness by the very news media that was deceived, speaks directly to Debord’s conception of the Spectacle and its capacity to dismiss any narrative that may destabilize the capitalist hegemony in the United States news media.